Fusobacterium nucleatum promotes chemoresistance to 5-fluorouracil by upregulation of BIRC3 expression in colorectal cancer - Sheng Zhang; Yongzhi Yang; Wenhao Weng; Bomin Guo; Guoxiang Cai; Yanlei Ma; Sanjun Cai (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Emerging evidence suggests a potential relationship between gut microbiota and the host response to chemotherapeutic drugs including 5-fluorouracil (5-Fu). Fusobacterium nucleatum (Fn) has been linked to the initiation and progression of colorectal cancer (CRC). Unfortunately, little was known about the relationship between Fn infection and chemotherapeutic efficacy. Here, we investigate the potential relationship between Fn infection and chemotherapeutic efficacy of 5-Fu in CRC. Methods Differentially expressed genes of CRC cell lines induced by Fn infection were analyzed based on a whole genome microarray analysis Then, we explored the relationship between upregulation of BIRC3 induced by Fn infection and chemoresistance to 5-Fu in vitro and in vivo. Furthermore, we dissected the mechanisms involved in Fn-induced BIRC3 expression. Finally, we investigated the clinical relevance of Fn infection, BIRC3 protein expression and chemoresistance to 5-Fu treatment in CRC patients. Results BIRC3 was the most upregulated gene induced by Fn infection via the TLR4/NF-κB pathway in CRC cells; Fn infection reduced the chemosensitivity of CRC cells to 5-Fu through upregulation of BIRC3 in vitro and in vivo. High Fn abundance correlated with chemoresistance in advanced CRC patients who received standard 5-Fu-based adjuvant chemotherapy after radical surgery. Conclusions Our evidence suggests that Fn and BIRC3 may serve as promising therapeutic targets for reducing chemoresistance to 5-Fu treatment in advanced CRC.